Improving Speaking skill by Using Modeling Strategy at the Grade Ten Students of SMK NMC Malang - Akhmad Sidiq (STKIP PGRI Jombang, 2018)
This study is aimed at developing strategy to improve the speaking skill of grade ten students SMK NMC Malang through modeling strategy. Modeling strategy is the strategy of giving examples, actions, and demonstrations of a certain topic in teaching speaking. The teacher should give a model how to practice the dialogue. This strategy is implemented in two cylces classroom action research (CAR), the researcher teaches the students while the teacher of the school act as the observer. The analysis of data uses qualitative and quantative data. The qualitative data are obtained from the observation sheet and field notes. The quantitative data are obtained through the observation checklist of the students’ involvement, tests, and questionnaire. The finding of this study indicated that the implementation of modeling strategy has improved the students’ speaking skill and the students’ learning motivation. It is also revealed that the students’ achievement of the second test with mean score 77.30 is better than the mean score of the first test 63. The questionnaire also proves that the students are interested in learning English after the implementation of the modeling strategy